Burden analysis of uterine fibroids and endometriosis in reproductive-age women globally, in China, India, and the United States, 1990–2021 - Chen, Yaru; Li, Qianyan; Liu, Mengjun; Niu, Ying; Liu, Hongli; Zhang, Lu (Frontiers in Nutrition, 2026)
BackgroundUterine fibroids and endometriosis are common benign gynecological diseases affecting the health of women of childbearing age, characterized by high incidence and recurrence rates. Despite the increasing global emphasis on women’s health, there is still a lack of systematic research on the burden these diseases impose on healthcare systems and society. This study is the first to comprehensively assess the disease burden on women of childbearing age globally, as well as in China, India, and the United States, from 1990 to 2021, and to predict future trends.MethodsBased on the Global Burden of Disease Study 2021 (GBD 2021) data, the incidence and age-standardized incidence rate (ASIR), disability-adjusted life years (DALYs), and age-standardized DALY rate (ASDR) were analyzed. Methods such as joinpoint regression, decomposition analysis, health inequality indices, and Bayesian age-period-cohort (BAPC) models were used to predict disease trends up to 2036.ResultsIn 2021, the global ASIR for uterine fibroids was 250.93 per 100,000 [showing an upward trend, estimated annual percentage change (EAPC) = 0.24], while the ASIR for endometriosis was 88.52 per 100,000 (showing a downward trend, EAPC = −1.00). The number of cases in China, India, and the United States accounted for nearly half of the global total. Decomposition analysis shows that population growth is the main cause of the burden of uterine fibroids, while epidemiological changes have alleviated the burden of endometriosis. The health inequality analysis indicates that the disease burden is heavier in high-Socio-Demographic Index (SDI) populations. Predictions show that by 2036, the global burden of uterine fibroids will continue to grow, while the burden of endometriosis will generally decline (except in the United States).ConclusionThe burden of uterine fibroids continues to increase, and although the burden of endometriosis has decreased, it remains severe. Targeted interventions are needed, including early screening, equitable distribution of medical resources, and country-specific strategies, to eliminate health inequalities and mitigate the long-term impact of these diseases on global women’s health.